Additions to the Ricciaceae flora of Rio Grande do Sul, including two remarkable records for the Brazilian liverwort flora - Ayub, Daniel Martins; Santos, Rinaldo; Costa, Denise (Phytotaxa, 2014)
The first record of Riccia boliviensis and R. iodocheila for Brazil and the first record of R. squamata and R. subplana for the liverwort flora of the state of Rio Grande do Sul are reported. The species were found during a floristic revision of the family Ricciaceae in the state. Taxonomic notes, photographs, habitat and geographic distribution are provided for each species.